Characteristics of refined lymphocyte subsets changes in people living with HIV/AIDS during antiretroviral therapy period: An observation from Wuhan, China - Yuan, Rui; Li, Ling; Hu, Wenjia; Zhuang, Ke; Zhang, Ejuan; Yan, Yajun; Feng, Ling; Chen, Xiaoping; Cao, Qian; Ke, Hengning; Gui, Xien; Yang, Rongrong (Frontiers in Immunology, 2023)
Background: To analyze the changing characteristics of continuous monitoring of refined lymphocyte subsets in people living with HIV/AIDS (PLWHA) during ART period. Methods: Refined lymphocyte subsets was continuously monitored using flow cytometry for 173 PLWHA, who were hospitalized in Zhongnan Hospital of Wuhan University from August 17, 2021 to September 14, 2022. The effect of ART status and duration of ART on changes of refined lymphocyte subsets were compared in different groups. Then, the levels of refined lymphocyte subsets in PLWHA treated for more than 10 years were compared to those of 1086 healthy individuals. Results: In addition to conventional CD4+ T lymphocytes and CD4+/CD8+ ratio, gradually increasing in numbers of CD3+CD4+CD45RO cells, CD3+CD4+CD45RA cells, CD45RA+CD3+CD4+CD25+CD127low and CD45RO+CD3+CD4+CD25+CD127low cells were found with the increase of ART duration. The number of CD4+CD28+ cells and CD8+CD28+ cells were 174/ul and 233/ul at 6 months post-ART, which gradually increased to 616/ul and 461/ul after ART initiation more than 10 years. Moreover, in ART≤6 months, 6 months-3years, 3-10 years and >10 years groups, the percentage of CD3+CD8+HLA-DR+/CD8 were 79.66%, 69.73%, 60.19% and 57.90%, respectively, and the differences between groups showed statistical significance (F=5.727, P=0.001). For those PLWHA with ART more than 10 years, the levels of CD4+ T lymphocytes, CD3+CD4+CD45RO cells, CD3+CD4+CD45RA cells, CD4+CD28+ cells and CD8+CD28+ cells can increase to levels similar to those of healthy control. However, for those PLWHA with ART more than 10 years, CD4+/CD8+ ratio was 0.86±0.47, which was lower than that of healthy control (0.86±0.47 vs 1.32±0.59, t=3.611, P=0.003); absolute counts and percentage of CD3+CD8+HLA-DR+ cells were 547/ul and 57.90%, which were higher than those of healthy control(547/ul vs 135/ul, t=3.612, P=0.003; 57.90% vs 22.38%, t=6.959, P<0.001). Conclusion: Persistent ART can gradually improve the immune status of PLWHA, which is manifested in the increase of lymphocytes, function recovery of lymphocytes and reduction of aberrant activation status of the immune system. After 10 years of standardized ART, most lymphocytes could return to levels of healthy persons, although it may take longer to complete recovery for CD4+/CD8+ ratio and CD3+CD8+HLA-DR+ cells.